Role of Leishmania (Leishmania) amazonensis amastigote glycosphingolipids in macrophage infectivity - Tanaka,A.K. (2007)
The role of glycosphingolipids (GSLs) present in amastigote forms of Leishmania (Leishmania) amazonensis during infection of macrophages was analyzed, with particular emphasis on GSLs presenting the terminal Galpß1-3Galpa disaccharide. Macrophage invasion by L. (L.) amazonensis amastigotes was reduced by 37% when the disaccharide Galpß1-3Galp (1 mM) was added to the culture medium. The putative macrophage receptor/lectin for ß-Gal-globotriaosylceramide (Galpß1-3Galpa1-4Galpß1-4Glc pß1-1Cer) and other structurally related GSLs from L. (L.) amazonensis amastigotes were analyzed by micelles and parasite binding assay to peritoneal macrophage proteins fractionated by SDS-PAGE under nonreducing conditions. Micelles containing purified amastigote GSLs or a suspention of L. (L.) amazonensis amastigotes fixed with 2% formaldehyde were incubated with nitrocellulose membrane containing the macrophage proteins transferred by Western blotting. Binding of micelles containing purified GSLs from amastigote forms or fixed L. (L.) amazonensis amastigotes to nitrocellulose membrane was probed using monoclonal antibody ST-3, which recognizes the glycoepitope Galpß1-3Galpa1-R present either in the micelle preparation or on the amastigote surface. Macrophage protein with molecular mass ~30 kDa bound the amastigote GSL and appeared to be a doublet on electrophoresis. The specificity of this interaction was confirmed using fixed L. (L.) chagasi amastigotes, which do not express GSLs such as ß-Galp-globotriaosylceramides, and which do not bind to 30-kDa protein.